The Urgency of Integrating Healthy Cities Policy Within Health Transformation in Indonesia - Bambang Setiaji; Muhammad Karyana; Anas Ma’ruf; Syahrul Aminullah; Kartika Dewi Puspa (Eduvest - Journal of Universal Studies, 2026)
Contemporary health development in Indonesia demands a paradigmatic shift from curative-centric focus toward strengthening promotive and preventive measures through regional-based approaches. This article aims to analyze the implementation of Healthy Cities (KKS) and formulate a strategic integration model into the National Health Transformation agenda. Utilizing a descriptive-analytical design with a literature-based policy study method, this research evaluated national policy documents, regional reports from Boyolali Regency and South Tangerang City, and Scopus-indexed international literature. Analysis indicates that while KKS has contributed to improved sanitation access and Green Open Space (RTH), implementation remains fragmented due to weak intersectoral policy coherence and limited performance indicators. As a solution, this study proposes "5 Pillars of Integration" encompassing intersectoral governance, healthy environment, healthy lifestyle behavior, promotive-preventive systems, and community participation. This synthesis demonstrates that KKS must be positioned as an upstream platform supporting the success of Pillar 1 (Primary Care) and Pillar 5 (Health Resilience) in health transformation. In conclusion, strengthening KKS through multi-level governance frameworks is crucial for creating resilient and sustainable health systems at the local level.